2008
DOI: 10.1097/ajp.0b013e31816b7cdf
|View full text |Cite
|
Sign up to set email alerts
|

Parents' Understanding of Information Regarding Their Child's Postoperative Pain Management

Abstract: Objectives-Unlike information provided for research, information disclosed to patients for treatment or procedures is largely unregulated and, as such, there is likely considerable variability in the type and amount of disclosure. This study was designed to examine the nature of information provided to parents regarding options for postoperative pain control and their understanding thereof.Methods-187 parents of children scheduled to undergo a surgical procedure requiring inpatient postoperative pain control c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 25 publications
2
38
0
2
Order By: Relevance
“…This finding is consistent with other studies (Choi et al, 2008;Tait et al, 2008;Twycross & Collis, 2013;Twycross & Finley, 2013) that have included some assessment of parental satisfaction with their child's pain management. Indeed, as seen in other studies, parents indicated that they would want the pain medicine given the same way in the future , despite most parents reporting that their child experienced significant postoperative pain (Twycross & Collis, 2013;Twycross & Finley, 2013).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding is consistent with other studies (Choi et al, 2008;Tait et al, 2008;Twycross & Collis, 2013;Twycross & Finley, 2013) that have included some assessment of parental satisfaction with their child's pain management. Indeed, as seen in other studies, parents indicated that they would want the pain medicine given the same way in the future , despite most parents reporting that their child experienced significant postoperative pain (Twycross & Collis, 2013;Twycross & Finley, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…On the basis of previous investigations of parent satisfaction with opioid administration (Bozimowski, 2012;Tait et al, 2008;Weldon et al, 1993), we hypothesized that parents of children in the PNCA-with-basal group and their nurses would have greater overall satisfaction and potentially more positive comments than parents and nurses of children in the other two groups. In addition, we expected parents and nurses to be least satisfied with the IV PRN opioid regimen.…”
Section: Introductionmentioning
confidence: 98%
“…Similar to previous data, 26 we found significant parental analgesic-related ADE knowledge deficits, even in parents who had received preoperative analgesic information and were preparing to make analgesic decisions following their child's surgery. We further demonstrated that Gist ADE Understanding was associated with a lower probability of giving opioids in the presence of nonserious as well as potentially serious ADEs.…”
Section: Analgesic Ade Knowledge and Trade-off Decisionssupporting
confidence: 90%
“…Items were adapted, in part, from a previous study that assessed parents' understanding of their child's pain management. 26 Our assessment of knowledge and understanding was based on fuzzy trace theory which has been used to examine and explain health care decisions. 23,34 This theory posits that information is coded into memory with differing precision ranging from verbatim knowledge (ie, very specific numerical risk information) to "fuzzy" or "gist knowledge" (ie, crude or categorical representations such as presence/ absence of an attribute or lower/higher risk).…”
Section: Instrument Developmentmentioning
confidence: 99%
See 1 more Smart Citation